PENGARUH LATIHAN SHUTTLE RUN TERHADAP KELINCAHAN ATLET KUMITE PUSAT PENDIDIKAN DAN LATIHAN PELAJAR (PPLP) KARATE DINAS PEMUDA DAN OLAHRAGA (DISPORA) RIAU - Salsabilah Salsabilah; Agus Sulastio; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aims to know the effect of shuttle run training (X) on the Agility (Y) of Kumite athletes at the Karate Education and Training Center (PPLP) of Riau Youth and Sports Agency (DISPORA). The method used in this research is an experimental method, with the research design used in this study is "One-Group Pretest Postest Design". The population of this study was the Kumite Athletes Student Education and Training Center (PPLP) Karate Department of Youth and Sports (DISPORA) Riau, in total 11 athletes. The instrument that used in this study was the Dodging Run Test. Data analysis and research hypothesis testing using independent t (t-test) with a significant level (α) of 0.05 with a confidence level of 0.95%. Based on data analysis with the results: Pre-test average 25.9 in the Post test 23.9 increased by 2 or 7.72% with the result (tcount 9.12> ttable 1.812), so Ho is rejected Ha accepted. Therefore it can be concluded that shuttle run training affects the agility of Kumite Athletes Student Education and Training Center (PPLP) Karate, Department of Youth and Sports (DISPORA) Riau.Key Words: Shittle Run, Agility, Athletes Kumite